Prices and Production. Monetary Theory of the Trade Cycle According to Friedrich August von Hayek - Appelt , Katarzyna (Studia Oeconomica Posnaniensia, 2015)
The article concerns the essence of the Austrian theory of the trade cycle. An expansion in banking credit leads to a divergence of the bank interest rate from the natural rate of interest. This has far-reaching implications for the economy. Among other things, it causes a misallocation of resources. Entrepreneurs undertake new investment projects, which cannot be finalized due to the rising costs of investment. Credit expansion initiates an economic boom, which is unavoidably followed by a period of recession. This modifies the structure of production, making it inadequate in terms of consumer preferences.